Discovery of a new class of non-â-lactam inhibitors of penicillin-binding proteins with Gram-positive antibacterial activity and oral bioavailability - O’Daniel, Peter I. (2014)
Infections caused by hard-to-treat methicillin-resistantStaphylococcus aureus(MRSA) are a serious global public-health concern,as MRSA has become broadly resistant to many classes of antibiotics. Wedisclose herein the discovery of a new class of non-β-lactam antibiotics,the oxadiazoles, which inhibit penicillin-binding protein 2a (PBP2a) ofMRSA. The oxadiazoles show bactericidal activity against vancomycin-and linezolid-resistant MRSA and other Gram-positive bacterial strains,invivoefficacy in a mouse model of infection, and have 100% oralbioavailability.